Severe MAC increases shear stresses on particles traversing the mitral valve: an in vitro study. (4th February 2022) - Pressman, GS; Darwish, A; Friend, EJ; Wiener, PC; Kadem, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Mitral annular calcification (MAC) is a strong predictor of stroke but mechanism(s) are poorly defined. Severe MAC can produce a gradient across the mitral valve (MV) and, when studied in vitro, disturbs normal flow across the valve resulting in increased viscous energy dissipation. Purpose: We hypothesized that severe MAC would increase shear stress on particles traveling across the MV into the left ventricle (LV). Given that shear stresses cause platelet activation this might represent a mechanism by which MAC could increase stroke risk. Methods: A silicone model MV was created using a 3D TEE dataset. 3D printed calcium phantoms were incorporated into the valve simulate severe MAC. The valve was tested in a left heart duplicator under rest and exercise conditions and compared with a duplicate valve without the calcium phantoms. Fine particles suspended in a water/glycerol blood analogue allowed for measurement of vortex formation and shear stresses using particle image velocimetry (PIV). Particle residence time (PRT) maps were created to assess how long blood particles would remain in the LV. Particle residence index (PRI - ratio of remaining particles in LV/initial number of particles) is a more quantitative measure of how fast particles leave the LV. These calculations were used to approximate viscous shear stresses on blood particles. For each particle the induced viscous shear stress was evaluated for the entire duration of residence in the LV. Results: For the normal MV all released particles left the LV by the 3rd cycle; with severe MAC particles completely left the LV shortly after the 7th cycle. PRI measurements confirmed that particles remained longer in the LV in the presence of severe MAC (figure 1). MAC also induced a shift in the accumulated shear stress levels from the high range > 0.4 Pa.s and the low range < 0.1 towards the middle region (0.16-0.32 Pa.s, figure 2). As shear stress is reported for one cycle, one may expect MAC to lead to higher accumulated higher viscous stresses as particles reside in the LV for a longer time. Conclusions: In the presence of severe MAC blood particles remain longer in the LV and are exposed to greater cumulative shear stresses vs the normal situation. Given that shear stress is known to cause platelet activation this may be a mechanism by which MAC increases risk of ischemic stroke.